Ochotona hyperborea subsp. hyperborea ... - Lissovsky, Andrey A.; Obolenskaya, Ekaterina V.; Dokuchaev, Nikolai E.; Okhlopkov, Innokentiy M. (Zenodo, 2021)
Ochotona hyperborea hyperborea (Pallas, 1811) Lagomys hyperboreus var. ferruginea Schrenk, 1858 Lagomys hyperboreus var. normalis Schrenk, 1858 Lagomys litoralis Peters, 1882 Ochotona kolymensis Allen, 1903 Ochotona hyperborea minima Sokolov et al., 1994 Ochotona hyperborea shamani Sokolov et al., 1994 Type.— Specimen unknown; the nominal taxon Lepus hyperboreus was described by P. S. Pallas on the basis of specimens collected by Carl Heinrich Merck (Pallas 1811:152). Type locality.— Chukchi Peninsula “terris Tschuktschicis” (Pallas 1811:152). This toponym can describe large territory; however, C. Merck only visited the northern part of Chukchi Peninsula along the trek from St. Laurent Bay–Mechigmen Bay (13–26 of September 1791)–Kolyutchin Bay (14 October)– Amguema River (18 November)–Chaun River (19 January 1792)–Anyuyskiy Ostrog at the estuary of Angarka River (14 February; 66.85°N, 164.25°E; Merck 1782–1792 [1980]). The detailed map of the route was published by Sarychev (1811). Merck mentioned Anyuyskiy ... : Published as part of Lissovsky, Andrey A., Obolenskaya, Ekaterina V., Dokuchaev, Nikolai E. & Okhlopkov, Innokentiy M., 2021, Intraspecific variation and taxonomy of northern pika Ochotona hyperborea (Mammalia, Lagomorpha), pp. 28-53 in Journal of Mammalogy 102 (1) on pages 36-37, DOI: 10.1093/jmammal/gyaa150, http://zenodo.org/record/7850862 ...